Overheating effect and hole-phonon interaction in SiGe heterostructures - Berkutov, I.B.; Andrievskii, V.V.; Komnik, Yu.F.; Myronov, M.; Mironov, O.A. (Физика низких температур, 2008)
The effect of the charge carriers overheating in a two-dimensional (2D) hole gas in a Si1–xGex quantum well, where x = 0.13; 0.36; 0.8, 0.95, has been realized. The Shubnikov–de Haas (SdH) oscillation amplitude was used as a «thermometer» to measure the temperature of overheated holes. The temperature dependence of the hole–phonon relaxation time was found using analysis of dependence of amplitude of SdH oscillations change on temperature and applied electrical field. Analysis of the temperature dependence of the hole–phonon relaxation time exhibits transition of 2D system from regime of «partial inelasticity» to conditions of small angle scattering.